2020
DOI: 10.1051/e3sconf/202017601007
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR/Cas9 for generation the cd209 knockout is a way to get cattle breeds resistant to the Bovine leukemia virus (BLV)

Abstract: Bovine leukemia virus (BLV) causes enzootic leukemia - a chronic infectious disease occurring against the background of embedding the virus in the genome of B-lymphocytes and leading to malignization, invasion of tumor cells in organs and the formation of tumors. The disease is common in the United States, Japan, and Asia. In Russia, up to 30% is infected with BLV. Moreover, there is evidence of the presence of antibodies to the BLV virus in some groups of people, and the relationship between BLV and cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Likewise, cells with overexpressed CAT1 levels became susceptible to BLV infection [43]. In addition to CAT1/SLC7A1, there is evidence that identifies the CD209 protein as a potential receptor for BLV [44,45]. CD209 is expressed in B-cells [45] and polymorphisms in its promoter has been linked to HTLV [46].…”
Section: Blv Phenotype Is Likely Affected By Various Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, cells with overexpressed CAT1 levels became susceptible to BLV infection [43]. In addition to CAT1/SLC7A1, there is evidence that identifies the CD209 protein as a potential receptor for BLV [44,45]. CD209 is expressed in B-cells [45] and polymorphisms in its promoter has been linked to HTLV [46].…”
Section: Blv Phenotype Is Likely Affected By Various Genetic Factorsmentioning
confidence: 99%
“…CD209 is expressed in B-cells [45] and polymorphisms in its promoter has been linked to HTLV [46]. More recently, a method has been developed to out the CD209 protein in hopes of creating cells that display resistance to BLV [44]. Although a definitive BLV receptor has not been identified in vivo, these two examples further suggest the influence of genetic regions outside aside from BoLA genes that influence BLV phenotype.…”
Section: Blv Phenotype Is Likely Affected By Various Genetic Factorsmentioning
confidence: 99%
“…Off-target mutations in human cancer cells have been attributed to sgRNA mismatching of dysfunctional repair mechanisms [ 173 ]. Similar off-targets have been observed in farm animals, including pigs and cattle [ 174 , 175 ], and non-specific editing has been detected in genome-edited mice [ 176 ]. Other studies have shown low or no detectable off-targets in genome-edited animals, possibly because it can be difficult to distinguish between off-targets and natural variations.…”
Section: Potential Concerns Associated With Crispr Cropsmentioning
confidence: 56%
“…Thus, this method was technically very difficult due to the inability to visualize pronuclei. In addition, it also had zero efficiency in case of editing the Cd209 gene [15]. The method of viral vectors had relatively low efficiency and undesirable side effects.…”
Section: Discussionmentioning
confidence: 99%